Howwa wheyya: Performance and gendered style in the Egyptian caricature - Essam, Hasnaa (AUC Knowledge Fountain, 2018)

(untitled)
This qualitative study explores linguistic styles and mis/communication as they relate to gendered performance in the context of Egyptian caricature. Within this context, seventy-four illustrations from The Piece of Paper by Gawish (2015) are subjected to discourse analysis. This type of caricature, as an example of performed speech, represents the perceptions of a group of Egyptian men, the cartoonist and his team, in depicting gendered daily-life interactions. The study investigates styles to examine the linguistic choices based on social groups such as women and men (Eckert and Rickford 2002: 26), and it explores gendered similarities as well as differences. The study focuses on social perceptions reflected in performed interactions for the significant relationship between perceptions and language practices in natural interactions (Tannen 1994: 139). It reveals the significance of the gendered use of the style of affective functions. Women are displayed as using more affective functions than men do. Women are shown to use more stylistic devices including asking questions, indirectness, verbal aggressiveness and repetition than men do. The image of miscommunication caused by the style of affective functions and its devices is clearly portrayed. Women are depicted as using physical aggressiveness against men, signifying the influence of affective functions and its devices on miscommunication. This study develops a deeper understanding of the overall picture of gender and language production in Egyptian Arabic.